NALAR ‘IRFANI: TRADISI PEMBENTUKAN DAN KARAKTERISTIKNYA - Nasrullah Nasrullah (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2013)
Leaning only to domination of the epistemology bayani and burhani is not enough. Both epistemology system must be completed with the epistemology of ’irfani which has a dimension of sprituality inmost. Logical reasoning system of the  epistemology  of  ’irfani  is  a  recontruction  of  the  pure  aspect  of  sprituality domain  to  get  God’s  knowledge  and  sense  of  humanity  through  authentic existential experinces